The cultural Politics of ‘Dutchness’ - Marc de Leeuw; Sonja van Wichelen (lo Squaderno, 2008)
To understand recent transformations of “Dutchness” it is crucial to look again to the development of Dutch liberalism. Both tolerance and liberalism are seen as Dutch accomplishments: from Holland as a free-haven for the religiously persecuted in the 17th century – of which Descartes and Spinoza are the most famous – to the image of progressive politics on sexuality, drugs, prostitution, and euthanasia.